ORNAMENT VARIETY OF ANIMALSON STONE COFFIN GRAVE (WARUGA); TRACES OF MINAHASA CULTURAL ACCULTURATION - Ronald Marthen Pieter Kolibu; Agus Sachari; Pindi Setiawan (Proceeding of International Conference on Art, Language, and Culture, 2019)
Examining the traces of cultural development in a community means also seeing how cultural acculturation plays a role in the formation of the cultural identity. Minahasa as a cultural community also cannot avoid the penetration of other cultural influences in the formation of Minahasa cultural identity. Megalithic cultural traces that are manifested in the tradition of burying corpses in stone coffin graves are cultural products that exist in Minahasa cultural community. From the beginning as a product of megalithic culture which tended to be plain without ornament variety, in its development the stone coffin graves of Minahasa people later developed into a cultural product that was rich in ornament variety. Knowledge of ornament variety, in the beginning, presented as an expression of Minahasa people. As the penetration of the cultural influences from other culture, the ornament variety on the stone coffin graves of Minahasa people, then more developed and varied. The ornament variety of animals is one of the many ornament types that was found in Minahasa stone coffin grave. The article is the result of a study that inventories various forms of animal ornament in Minahasa stone coffin grave, which then with qualitative research methods and an interpretive approach interpreting the ornament variety of animals in Minahasa stone coffin grave. The focus of the study results is to reveal the meaning that is to be conveyed with the presence of this animal ornament. Interpretation of meaning is obtained through interviews and literature studies that are conducted in this study. The difference in interpretation is one of the challenges in this study. So that the meaning disclosure by the researchers is not absolute, but it still provides a different interpretation space along with the process that are carried out in this study.